P-T estimates of peak Bushveld metamorphism in the eastern Bushveld complex, Limpopo Province, South Africa : constraints from P-T pseudosections - Roberts, R.J. (James) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.